Decommissioning Planning of Offshore Oil and Gas Fields in Vietnam: What Can be Learnt from Mine Closure Planning in Scotland? - Le, Huyen Thi; Liao, Janet Xuanli; Spray, Christopher J. (International Journal of Energy Economics and Policy, 2021)
Due to the lack of necessary requirements in the existing regulations for decommissioning of offshore oil and gas fields in Vietnam, this paper makes policy recommendations based on the comparison between the decommissioning planning of offshore oil and gas fields in Vietnam and the similar closure planning of opencast coal mines in Scotland. The comparative analysis shows that there is interplay between the project context and restoration/decommissioning outcomes in the cases of three opencast coal mines in East Ayrshire, Scotland and X oil field in Vietnam. The influencing contextual factors in both cases can be categorized as biophysical and material conditions, community attributes, biodiversity’s interest, socioeconomic context and rules. Based on such analysis, additional issues should be considered while preparing future decommissioning plans and updating relevant laws in Vietnam. Particular challenges include compliance monitoring, shell mounds, drill cuttings, financial assurance, consultation with local communities and recognition of their interests, rigs-to-reefs, coastal communities’ socioeconomic development, and investment in research, training and education about oil and gas decommissioning. Keywords: Offshore Platforms, Opencast Coal Mines, Decommissioning Planning, Closure Planning, Decommissioning Outcomes, JEL Classifications: L52, O21, O25 DOI: https://doi.org/10.32479/ijeep.11196